Advance care planning in dementia care: Wants, beliefs, and insight. (May 2022) - Tetrault, Annika; Nyback, Maj-Helen; Vaartio-Rajalin, Heli; Fagerström, Lisbeth
Background: Advance care planning gives patients and their family members the possibility to consider and make decisions regarding future care and medical procedures. Aim: To explore the view of people in the early stage of dementia on planning for future care. Research design: The study is a qualitative interview study with a semistructured interview guide. The data were analyzed according to the Qualitative Analysis Guide of Leuven. Participants and research context: Dementia nurses assisted in the recruiting of people with dementia for participation in the study. Study information was mailed to 95 people with early stage dementia. Ten people with dementia and eight caregiver spouses participated in the study. Ethical considerations: People with dementia belong to a vulnerable patient group, and care was taken in the areas of informed consent and accessible information. Findings: The views of people with dementia are characterized by a complex storyline involving tensions and movement within the themes of wants, beliefs, and levels of insight. Participants wanted to think about the future but also wanted to live in the here and now. Discussion: High demands are placed on the advance care planning process for people with dementia and their family caregivers. A dignity-enhancing approach in dementia care emphasizes the dignity of and respect for this vulnerable and care-dependent patient group. Conclusion: The process of advance care planning in dementia care needs to go beyond person-centered care to a relationship-centered process. The illness trajectory and the impact on autonomy need to be taken into consideration.